Impact of Numerical Variation in fms-like Tyrosine Kinase Receptor Internal Tandem Duplications on Clinical Outcome in Normal Karyotype Acute Myelogenous Leukemia - Borthakur, Gautam (2012)
BACKGROUND: Impact of single versus multiple fms-like tyrosine kinase receptor 3 internal tandem duplication (FLT3-ITD) mutations on clinical outcomes of patients with acute myelogenous leukemia is not well studied particularly while simultaneously accounting for the quantitative mutation burden. METHODS: We performed a multi-variate analysis for overall (OS), event free (EFS) and remission duration (CRD) including numerical variation (single versus multiple) and quantitative mutant burden of FLT3-ITD as variables among other clinically relevant variables. RESULTS: Our analysis of a cohort of 1043 patients with AML showed that among patients with normal karyotype (NK-AML) and FLT3-ITD mutation, overall survival and event-free survival are not affected by the number of FLT3-ITD mutations but remission duration (CRD) is significantly longer in patients with multiple FLT3-ITD mutations (median CRD 86 weeks vs 34 weeks, p=.03). CONCLUSION: In time to event analysis of patients with NK-AML and FLT3-ITD mutation, number of mutations and mutant burden should be considered among other factors.